MEDICATION OVERUSE HEADACHE: PRACTICAL GUIDELINES - A. V. Sergeev; V. A. Parfenov (Медицинский совет, 2018)
Medication overuse headache (MOH) is defined as a secondary/symptomatic headache when HA occurs on 15 or more days per month, when the therapeutic agent is used excessively for three or more months. MOH is often combined with chronic forms of primary HA (chronic migraine and chronic tension headache). About 1% of the population periodically receives about 10 tablets of various analgesics per month. Due to high prevalence, high social and economic costs, high rates of recurrence, MOH represents a significant problem for both the health care system and practitioners. The review discusses issues of epidemiology, mechanisms of formation, diagnostic criteria and the most effective approaches to the treatment of MOH.